Privacy cloud storage scheme based on fog computing - Jiyuan ZHOU; Hao LUO; Lei QIU; Tian WANG (物联网学报)
As one of the core applications in cloud computing field,cloud storage attracts a large number of users depending on its powerful storage capacity.However,in this storage schema,users’ data is stored completely in cloud server.In other word,users’ right of control on data is lost and users are facing privacy leakage risk.Traditional privacy protection scheme is usually based on encryption technology,but the attack from the inside of cloud server can’t be resisted effectively by these kinds of methods.Once the password gets compromised,users’ data will be stolen.In order to solve this problem,a three-level secure cloud storage scheme based on fog computing was proposed and a Hash-Solomon code algorithm was designed.A small part of data was stored in local machine and fog server,which can take full advantage of cloud storage and protect the privacy of data.Through the theoretical safety analysis and experimental test,the feasibility of our scheme is proved,and it is really a powerful supplement to existing cloud storage scheme.